2001
DOI: 10.3171/jns.2001.94.2.0224
|View full text |Cite
|
Sign up to set email alerts
|

Basal ganglia hematomas in severely head injured patients: clinicoradiological analysis of 37 cases

Abstract: Traumatic basal ganglia hematomas are dynamic lesions that tend to enlarge during the acute posttraumatic period. The overall prognosis in this series was poor. Patients in whom the volume of the hematoma was larger than 25 ml and those in whom hematoma volume enlargement or raised intracranial pressure occurred had the worst outcomes, perhaps indicating the need for a more aggressive surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
2
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(97 citation statements)
references
References 31 publications
(36 reference statements)
3
91
2
1
Order By: Relevance
“…[2][3][4][5][6][7][8]13,16,[19][20][21] As we observed in the present case, many studies have shown a favorable outcome for patients with TBGH. …”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8]13,16,[19][20][21] As we observed in the present case, many studies have shown a favorable outcome for patients with TBGH. …”
Section: Resultssupporting
confidence: 71%
“…18 The management of the TBGH depends on the neurological status, size of the hematoma, presence of mass effect, and the options include conservative management, open surgery, CT-guided stereotactic, or ultrasound-guided aspiration. [2][3][4]10 In present case, in view of the smaller size of the lesion, we managed the patient conservatively. Traumatic basal ganglia hemorrhage needs to be differentiated from jpmer spontaneous basal ganglionic hematomas.…”
Section: Discussionmentioning
confidence: 99%
“…The pioneering work of Adams et al [2] in 1986 identified TBGH as a distinct diagnosis rather than a spectrum of severe head injuries or diffuse axonal injuries, which was subsequently confirmed by many [1,5,6,7]. Its is mostly encountered in high-velocity trauma; however, falls from height are a frequent cause as well in children as recorded in 38% of our patients, which is similar to other studies [1,5,6,7,8,9]. …”
Section: Discussionmentioning
confidence: 97%
“…In 1980 Maki et al [3], in their study on 7 children, reported the role of anterior stretch on the lateral branches of the perforators of the middle cerebral artery in traumatic TBGH. Boto et al [5], in 2001, reported the role of acceleration and deceleration during trauma as a cause of stretching and tearing of pallidal branches of the anterior choroidal artery, which produces small multiple hematomas and contusions in the region of the basal ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…After complete clinical and neurological evaluations were peformed, computed tomography (CT) scans were regularly obtained and the volume of the hematomas, as well as presence or absence of hydrocephalus were considered. The volume of the hematomas was measured according to the formula: length x width x height x 0.5 [10][11][12] . Both, length and width, were obtained from the CT slices demonstrating the largest hyperdense area of the hematomas.…”
Section: Methodsmentioning
confidence: 99%